Reading computer-generated texts: examining code as a reading strategy - Hongisto Tuuli (Taylor & Francis, 2025)
This article explores code as part of a reading strategy, focusing on a case study of works produced as part of a programming challenge entitled National Novel Generation Month (NaNoGenMo). For the challenge, participants needed to develop a programme that produces an output, most often a creative text, and make both the output and its source code available to readers. I approach the NaNoGenMo texts as works involving multiple audiences with different capabilities. I argue that examining the code alongside the produced text is a reading strategy that offers a different reading experience than that of reading the work without the code and that the source code can provide insights into the work’s authorial intention. As computer-generated texts are becoming increasingly ubiquitous, discussion of their authorship is as relevant as ever. This article offers one perspective on this discussion and on the significance of authorial intention in computer-generated works.